A study of nasotracheal intubation using bougie technique and video laryngoscope: an observational study - Gautam, Shailendra Nath; Koju, Srijana; Agrawal, Ankit; Shah, Jyoti; poudel, Anju (Birat Journal of Health Sciences, 2025)
Introduction: Nasotracheal intubation (NTI) is a widely used technique in maxillofacial and oral cavity surgeries to provide better surgical access. Conventional NTI, while effective, is associated with complications such as nasal bleeding and oral cavity trauma. The bougie-assisted NTI technique, combined with video laryngoscopy, has been proposed to improve the success rate of firstattempt intubations and reduce trauma and other complications. Objectives: The study aimed to evaluate the effectiveness and safety of the bougie-assisted NTI technique, focusing on the success rates of first and second intubation attempts, time required for intubation, hemodynamic changes, and incidence of complications like nasal bleeding and mucosal injury. Methodology: This prospective observational study was conducted at Nepal Medical College from February 2024 to July 2024. A total of 36 patients, aged 18 years or older, scheduled for elective maxillofacial and oral cavity surgeries were included. The bougie-assisted technique was adopted under general anesthesia, and video laryngoscopy was employed for visualization. Hemodynamic parameters and complications were recorded at predefined intervals. Data were analyzed using descriptive statistics. Results: Among 36 patients who underwent nasal intubation, 28 patients (77.8%) were successfully intubated on the first attempt, and 8 patients (22.2%) required a second attempt, There were no cases of esophageal intubation, or oral cavity injury. The incidence and severity of nasopharyngeal trauma was significantly decreased. The heart rate, systolic blood pressure, have no significant change (p< 0.05), But the diastolic blood pressure increase in 10,and 15 minutes was significant (P > 0.05) in pre-intubation and post-intubation hemodynamic. The aim of the study was bougie-assisted technique would result less hemodynamic change, easy to intubate, less time required to intubate without nasopharyngeal trauma. Conclusion: Bougie assisted technique for nasotracheal intubation increases the rate of success on first attempt while reducing complications such as nasal or oral trauma and epistaxis. Therefore, we recommend using the bougie assisted technique for nasal intubation.